P-74 GLYCOSYLATED HEMOGLOBIN LEVELS AS A PREDICTOR OF HEPATIC FIBROSIS DUE TO MASLD - Stefanny Cornejo Hernández; Esly Esquivel Alarcón; Reyna Hernández Espinoza; Juan Salvador García Hernández; Mayra Gabriela García Araiza; Trinidad Baldovinos Hernández; Javier Bastida Alquicira; Eira Cerda Reyes; Adriana Martinez Cuazitl (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Hepatic steatosis associated with metabolic dysfunction (MASLD) has a prevalence of 30% worldwide, and 80% of these patients do not present alterations in liver biochemistry. One of the cardiometabolic criteria is having glycosylated hemoglobin ≥5.6%, so an analysis was carried out using the ADA criteria for the diagnosis of prediabetes with HbA1C levels 5.7% - 6.4% and the degree of liver fibrosis. Objectives: Compare the values of glycosylated hemoglobin and fibrosis determined by Transient Elastography. Patients / Materials and Methods: Patients with MASLD criteria were included who underwent Transient Liver Elastography (Fibroscan ® 630 Expert v10720), APRI, FIB4, NAFLD score, blood count, liver biochemistry, lipid profile, glucose, glycosylated hemoglobin, clotting times. (TP, INR). It was compared with a control of healthy people. For statistical analysis, SPSS V24 was used for continuous quantitative variables expressed as mean and percentage, with moderate Spearman's Rho correlation. Results and Discussion: Seventy-five patients with steatosis determined by CAP ≥ 232 were included. The age of the patients was 45 (40, 50).Patients were classified as healthy (HbA1C <5.7%), prediabetic (HbA1C 5.7%-6.4%), diabetic (HbA1C >6.5%), and patients with a previous diagnosis of diabetes were classified as diabetic controlled (HbA1C <7%). and uncontrolled diabetics (HbA1C >7%), HbA1C levels were 5.7% (5.4%-5.9%). According to the MASLD criteria, 25 patients had HbA1C < 5.6% and 50 with HbA1C > 5.6% or with treatments for T2D.Sixty-five patiens (86.7%) had no fibrosis, and 10 (13.3%) had fibrosis, with 5.1 kPa (4.3 kPa, 6.5 kPa).Although no association was found between the degree of steatosis and the degree of fibrosis, the patient with the highest level of fibrosis presented the highest degree of steatosis. X2= 8.916, p=0.178No association was found between the degree of steatosis and diabetes.X2= 11.723,p=0.068However, the degree of diabetes is associated with the presence of fibrosis and the degree of fibrosis, with a weak positive correlation existing between HbA1C levels and CAP levels, Spearman's rho 0.280 p=0.015. Tables 1 and 2Although no assessment was found between BMI and kPa to determine if there is an association between the degree of fibrosis and the nutritional level, curiously, it can be observed that a healthy patient with grade 3 fibrosis has uncontrolled diabetes. Table 3 Conclusions: Prediabetes may be a predictor of the presence of liver fibrosis associated with MASLD.